Mothers’ Experience of Social Change and Individualistic Parenting Goals Over Two Generations in Urban China - Bian, Qinglin; Chen, Yuyan; Greenfield, Patricia M.; Yuan, Qinyi (Frontiers in Psychology, 2022)
During the past four decades, China has gone through rapid urbanization and modernization. As people adapt to dramatic sociodemographic shifts from rural communities to urban centers, individualistic cultural values in China have increased. Meanwhile, parent and child behavior in early childhood have also evolved accordingly to match a more individualistic society. This mixed-method study investigated how social change in China may have impacted parenting goals and child development in middle childhood, as seen through the eyes of the current generation of mothers. Thirty mothers of fifth grade elementary school students from Shenzhen, China were recruited and took part in semi-structured interviews. Participants answered questions and provided examples about their children’s life, their own childhood, and the perceived differences between the two generations. Participating mothers were also asked to rate which generation, themselves or their parents, cared more about the childrearing goals of academic competitiveness and socioemotional well-being. Using both qualitative and quantitative analysis, we expected and found an intergenerational increase in the perceived value mothers placed on individualistic traits: Current mothers care more about their children’s academic competitiveness, personal happiness, and social adjustment, compared to their experience of their own mothers' attitudes during their childhood a generation earlier. Moreover, we found an expected intergenerational increase in perceived conflict between the children’s academic competitiveness and socioemotional wellbeing.